Suitability of Land for Forage Crops in Bangko Hamlet, Bobane Igo Village, South Jailolo District, West Halmahera Regency - Hartono, Gunawan; Robo, Sarif; Sulasmi, Sulasmi (Agrikan Jurnal Agribisnis Perikanan, 2024)
The availability of high-quality and sustainable livestock feed remains a major challenge in the development of the livestock sector, particularly in West Halmahera. One of the key factors affecting livestock feed availability is land suitability for forage crop cultivation. Bangko Hamlet in Bobane Igo Village possesses extensive land potential, but its utilization has not been optimized. This study aims to evaluate the suitability of the area’s land for forage crops such as Calliandra, Leucaena, and Napier grass. The research employed the matching method, comparing land characteristics with land suitability criteria. The results indicate that the actual land suitability ranges from S2 (moderately suitable) to N1 (not suitable). The main limiting factors identified include water availability (dry months and rainfall), erosion levels, nutrient retention (base saturation and organic matter content), and topography affecting drainage and slope. Improvement efforts such as fertilization, water management, soil conservation, and erosion control can enhance potential land suitability to the S2 class. This study recommends management strategies based on limiting factors to support sustainable land utilization and meet the livestock feed demand in the area.